Questionnaire: Level of knowledge of the urban population about agroecological foods - Vivas-Vivas, Ramiro José (2022)
Introduction. Food consumption affects the environment, so it is necessary to investigate what level of knowledge the urban population has about the origin of the food they consume. Objective. To design, validate, and determine the reliability of an instrument to assess the level of knowledge that the urban population has regarding agroecological foods. Materials and methods. The work was developed at the Universidad Central de Ecuador in Quito, Ecuador, during the period 2020-2021. The type of research was exploratory-descriptive, with a non-experimental design and stratified non-probabilistic sampling. The content of the instrument was evaluated using the Delphi method with the participation of seventeen experts. Two pilot tests were applied to 370 and 1323 participants. The internal consistency and the homogeneity index were determined using Cronbach’s Alpha. The dimensionality of the construct was established with the Cronbach-Mesbah curve. Construct validity was assessed with factor analysis. Results. The content validity showed a value greater than 75 % of convergence between experts. In the internal consistency validation, Cronbach’s Alpha was 0.9 and the homogeneity index was greater than 0.2. In the study of the dimensionality of the construct, the Cronbach-Mesbah curve indicated that the unidimensionality was fulfilled throughout the instrument. In the construct validity in the factor analysis, it was observed that the Kaiser-Meyer-Olkin measure was 0.753. Bartlett’s sphericity was 0.000 and the factor extraction test was greater than 77 %. Conclusions. The instrument achieved high validity and reliability both in its content assessed by experts, and in its internal consistency, dimensionality, and construct validity performed by statistical methods. The instrument is reliable and can be applied in the urban population.